Enhancing nutritional value and health benefits of gluten-free confectionery products: innovative pastilles and marshmallows - Pronina, Yuliya; Belozertseva, Olga; Nabiyeva, Zhanar; Pirozzi, Annachiara; Carpentieri, Serena; Ferrari, Giovanna; Bazylkhanova, Elmira; Burlyayeva, Anastasiya (Frontiers in Nutrition, 2024)
The research focuses on enhancing the nutritional value and potential health benefits of gluten-free confectionery products, developing innovative pastilles and marshmallows enriched with medicinal herb extracts, probiotics, and bioactive compounds from natural sources. Physicochemical properties, including water activity, texture, and color, are assessed to evaluate the quality of the final products. Moreover, in vitro digestibility of the confectionery products is also investigated, with a focus on the release of bioactive compounds such as total phenolic compounds (TPC) and total anthocyanin (TAC) during simulated gastrointestinal digestion. Results indicate that the addition of specific ingredients to pastille samples does not lead to variations in water activity (~ 0.44), preserving the original properties, quality, and stability of the food. In contrast, the incorporation of additives in marshmallow products significantly increases water activity (p ≤ 0.05), attributed to their moisture-retaining effect. In general, our findings reveal that texture properties and color parameters are significantly affected by different formulations (p ≤ 0.05) for both confectionery products. Notably, the use of fruit and berries puree, along with the incorporation of additives, improves the functionality of confectionary products in terms of consumer acceptance (harder pastilles and softer marshmallow) and product quality. Furthermore, the study reveals that bioactive compounds are released and become more bioaccessible during digestion, particularly in the intestinal phase, with a maximum release exceeding 97% of TPC and TAC for both pastille and marshmallow samples. These findings pave the way for the development of a new category of gluten-free confectionery products, enriched with functional ingredients that offer potential health benefits, aligning with consumer preferences for natural, functional, and health-conscious treats. This research contributes to the evolving the landscape of functional confectionery products and underscores their potential as immune-boosting and naturally based food options.